2009
DOI: 10.1159/000215593
|View full text |Cite
|
Sign up to set email alerts
|

Skin Care in the NICU Patient: Effects of Wipes versus Cloth and Water on Stratum Corneum Integrity

Abstract: Background: NICU patients are at risk of skin breakdown due to prematurity, irritant exposure, medical status and stress. There is a need to minimize damage, facilitate skin development and reduce infection risk, but the literature on the effects of skin care practices in NICU patients is limited. Objectives: To test the hypothesis that baby diaper wipes with emollient cleansers and a soft cloth would minimize skin compromise relative to cloth and water. Methods: In 130 NICU infants (gestational age 23–41 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(110 citation statements)
references
References 82 publications
(39 reference statements)
2
106
1
1
Order By: Relevance
“…The high device-related PUs in pediatrics is distinct from that of adults 16,29,32,33 and may indicate a susceptibility to iatrogenic injury in pediatrics, perhaps resulting from physiologic differences between adult and pediatric skin. [13][14][15][34][35][36][37][38] Our NICU stage II device-related PU level is higher than in other reports. Fisher et al 39 found 88% stage I ulcers from facemasks.…”
Section: Discussioncontrasting
confidence: 68%
“…The high device-related PUs in pediatrics is distinct from that of adults 16,29,32,33 and may indicate a susceptibility to iatrogenic injury in pediatrics, perhaps resulting from physiologic differences between adult and pediatric skin. [13][14][15][34][35][36][37][38] Our NICU stage II device-related PU level is higher than in other reports. Fisher et al 39 found 88% stage I ulcers from facemasks.…”
Section: Discussioncontrasting
confidence: 68%
“…42 The immature SC of premature infants is functionally compromised for several weeks with estimates of full maturation time varying from 2 to 9 weeks postnatal age 49,50 and even longer (months) for complete acid mantle formation. 51 The effect of epidermal maturation in the absence of vernix, as seen in infants < 28 weeks, is unknown. Evidence suggests that epidermal barrier formation in premature infants is a wound repair process.…”
Section: Ontogeny Of Barrier Maturationmentioning
confidence: 99%
“…Even routine care, such as changing and bathing, can provoke skin irritation, due to compromised skin barrier function [3]. Special skin care regimens and incubator practices are mandatory to optimize and protect postnatal skin barrier function [3,4,5]. However, no scientifically based guidelines for standard skin care have yet been established for preterm infants, as few data are available about the maturation of skin barrier in this age group.…”
Section: Introductionmentioning
confidence: 99%